Effects of Distal and Proximal Variables on Donating Behavior - Cristiane Matinez de Almeida; Vivianni Veloso; Carla Cristina Paiva Paracampo (Psicologia: Teoria e Pesquisa)
Abstract Two experiments involving donation were conducted. Experiment 1 examined whether college students would primarily retain tokens for themselves or donate them to relatives and strangers, which could be exchanged for items obtained in a game. The results showed 57% retained more tokens for themselves or donated to relatives; 28% to strangers, and 15% the same amount to themselves and strangers or to relatives and strangers. Experiment 2 examined whether the tendency to donate in a given direction would change after reading a text with justifications for donating to strangers. A significant difference was observed between Experimental Groups 1 and 2 (p < 0.003), with fewer tokens donated to relatives or retained for oneself after exposure to the text. It is concluded that human generosity is influenced by the evolutionary history of the species and the human cultural and verbal environment.